Hepatitis D virus replication is sensed by MDA5 and induces IFN-β/[lambda] responses in hepatocytes - Zhang, Zhenfeng; Filzmayer, Christina Annette Heidi; Ni, Yi; Sültmann, Holger; Mutz, Pascal; Hiet, Marie-Sophie; Bartenschlager, Ralf; Urban, Stephan (Journal of hepatology, 2018)
Background & Aims Hepatitis B virus (HBV) and D virus (HDV) co-infections cause the most severe form of viral hepatitis. HDV induces an innate immune response, but it is unknown how the host cell senses HDV and if this defense affects HDV replication. We aim to characterize interferon (IFN) activation by HDV, identify the responsible sensor and evaluate the effect of IFN on HDV replication. Methods HDV and HBV susceptible hepatoma cell lines and primary human hepatocytes (PHH) were used for infection studies. Viral markers and cellular gene expression were analyzed at different time points after infection. Pattern recognition receptors (PRRs) required for HDV-mediated IFN activation and the impact on HDV replication were studied using stable knock-down or overexpression of the PRRs. Results Microarray analysis revealed that HDV but not HBV infection activated a broad range of interferon stimulated genes (ISGs) in HepG2NTCP cells. HDV strongly activated IFN-β and IFN-λ in cell lines and PHH. HDV induced IFN levels remained unaltered upon RIG-I (DDX58) or TLR3 knock-down, but were almost completely abolished upon MDA5 (IFIH1) depletion. Conversely, overexpression of MDA5 but not RIG-I and TLR3 in HuH7.5NTCP cells partially restored ISG induction. During long-term infection, IFN levels gradually diminished in both HepG2NTCP and HepaRGNTCP cell lines. MDA5 depletion had little effect on HDV replication despite dampening HDV-induced IFN response. Moreover, treatment with type I or type III IFNs did not abolish HDV replication. Conclusion Active replication of HDV induces an IFN-β/λ response, which is predominantly mediated by MDA5. This IFN response and exogenous IFN treatment have only a moderate effect on HDV replication in vitro indicating the adaption of HDV replication to an IFN-activated state. Lay summary In contrast to hepatitis B virus, infection with hepatitis D virus induces a strong IFN-β/λ response in innate immune competent cell lines. MDA5 is the key sensor for the recognition of hepatitis D virus replicative intermediates. An IFN-activated state did not prevent hepatitis D virus replication in vitro, indicating that hepatitis D virus is resistant to self-induced innate immune responses and therapeutic IFN treatment.